Evaluating the Creativity of a Product Using Creativity Measurement Tool - Siti Norzaimalina, Abd Majid; Hafizoah, Kassim; Munira, Abdul Razak (2015)
This paper discusses the creativity evaluation of a mechanical engineering product namely “Rocket Motor” by using a quantitative measurement tool, which is a web-tool called Creativity Measurement Tool (CMeT). This tool is useful to measure product creativity based on four dimensions: Novelty, Usability, Effectiveness and Aesthetic Value. Each dimension encompasses several characteristics that are significant to assess the creativity of the product. A total of 100 novice respondents from engineering field were asked to rate the product on a scale from 1 to 4 with detailed descriptive of each scale for each characteristic. The results are reported in percentages according to each dimension and the overall score. Based on the CMeT result, the inventor can identify which dimensions that need to be emphasised and improvised.